A multi-level porous MOFs material containing CuRu bimetallic and its preparation method and application

By introducing Ru3+ into Cu-BTC MOFs material and forming CuRu bimetallic MOFs material, the problems of the decrease in specific surface area and lack of multi-stage pore structure of Cu-BTC materials are solved, and the effect of significantly improving separation efficiency and catalytic activity is achieved.

CN115260513BInactive Publication Date: 2025-03-04GUANGDONG UNIV OF PETROCHEMICAL TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210907865.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The decline in specific surface area and lack of multi-stage porous structure of existing Cu-BTC MOFs materials limit their application performance in the fields of gas storage and separation.

Method used

By introducing Ru3+ to the Cu-BTC frame metal node, replacing the Cu2+ unsaturated site, a CuRu bimetallic MOFs material containing Cu-Cu, Cu-Ru and/or Ru-Ru structures is formed, and a multi-stage pore structure is formed by controlling the reaction conditions.

Benefits of technology

The multi-stage pore structure formation of CuRu bimetallic MOFs material has been achieved, which significantly improves its separation efficiency and catalytic activity, and is suitable for the fields of propylene gas separation and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115260513B_ABST
    Figure CN115260513B_ABST
Patent Text Reader

Abstract

The present invention discloses a hierarchical porous MOFs material containing CuRu bimetal, a preparation method thereof, and an application thereof. The hierarchical porous MOFs material containing CuRu bimetal of the present invention has a chemical formula of [Cu 2+ x Ru x (BTC)2I x n , where 0.03 < x < 0.15, n is an integer greater than 10000, and I is at least two of Cl ‑ , NO3 ‑ , Ac ‑ , OH ‑ . The present invention introduces Ru 3+ into the Cu-BTC framework metal node, realizes the replacement of the Cu 3+ unsaturated sites at the metal node with Ru 2+ , forms a MOFs material containing CuRu bimetal with a structure including Cu-Cu, Cu-Ru, and / or Ru-Ru structures, and at the same time, mesopores are formed in the MOFs material, which is a hierarchical porous MOFs material. The hierarchical porous MOFs material containing CuRu bimetal of the present invention is a heterogeneous catalyst, and the separation efficiency and catalytic activity are significantly improved.​
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal organic framework materials, and more specifically to a multi-level porous MOFs material containing CuRu bimetallic materials, and a preparation method and application thereof. Background Art

[0002] MOFs materials have high specific surface area, controllable chemical composition and pore structure, and have broad application prospects in many fields such as gas storage and separation, heterogeneous catalysis, and drug sustained release. In addition, specific MOFs structures and compositions can be designed and synthesized according to specific application requirements. For example, the multi-level pore size and chemical composition can be adjusted by introducing mixed metals and defective ligands. n ) is a classic structure among many MOFs. The BET specific surface area of ​​the parent structure is 900-1800m 2 ·g -1 range, which only contains regular microporous structures (pore diameter is about 0.7-0.8nm) and contains a large amount of coordinated unsaturated Cu 2+ sites and trace amounts of Cu + Defective site.

[0003] Controllable regulation of the structure and composition of MOFs to adapt to specific applications remains a great challenge. So far, existing technologies have reported that the structure and composition of MOFs can be regulated through strategies such as template method (RSC Adv., 2017, 7, 52245-52251), introduction of coordination regulators (Angew. Chem. Int. Ed., 2017, 56, 563-567), introduction of defective ligand design (Angew. Chem. Int. Ed., 2014, 53, 7058-7062), synthesis under high pressure CO2 conditions (Nat. Commun., 2014, 5, 5465), ozone post-treatment (J. Am. Chem. Soc., 2018, 140, 15022), and mixed metal introduction (J. Phys. Chem. C., 2018, 122, 21433). However, the microporous structure and single Cu 2+ The metal sites obviously limit the application performance and scope of Cu-BTC, especially for large substrate molecules.

[0004] In 2018, Wolfgang Kleist et al. (Dalton Transaction, 2015, 44(5), 2052) synthesized [(Cu 3-x Ru x (BTC)2] nMOF structure, but its BET specific surface area is significantly reduced to 570 m 2 ·g -1 Nearby, it is possible that part of the Ru 3+ is not on the metal nodes of the framework, but is filled in the pores in the form of oxides.

[0005] Therefore, using Ru 2+ / Ru 3+ to replace part of the Cu on the metal nodes of the parent Cu-BTC structure 2+ , and keeping the BET specific surface area from decreasing significantly, while introducing a hierarchical pore structure at the same time, is still a very challenging task. Summary of the Invention

[0006] The present invention aims to overcome the defects of the decreased specific surface area and the absence of hierarchical pore structure of the MOFs containing CuRu bimetals in the above-mentioned prior art, and provides a preparation method of a hierarchical pore MOFs material containing CuRu bimetals.

[0007] Another object of the present invention is to provide a hierarchical pore MOFs material containing CuRu bimetals prepared by the above preparation method.

[0008] Another object of the present invention is to provide the above hierarchical pore MOFs material containing CuRu bimetals for use as an odor adsorbent in the field of propylene / propane gas separation.

[0009] To solve the above technical problems, the technical solution adopted by the present invention is:

[0010] A hierarchical pore MOFs material containing CuRu bimetals, characterized in that its chemical formula is [Cu 3-x Ru x (BTC)2I x n , where 0.03 < x < 0.15, n is an integer greater than 10000, and I is at least two of Cl - , NO3 - , Ac - , OH - .

[0011] The present invention realizes replacing the Cu at the metal nodes with Ru by introducing Ru 3+ into the metal nodes of the Cu-BTC framework 3+ . 2+ ​Unsaturated sites are formed to form a MOFs material containing CuRu bimetallics and containing Cu-Cu, Cu-Ru and / or Ru-Ru structures, and the MOFs material also has mesopores, which is a multi-level porous MOFs material. The multi-level porous MOFs material containing CuRu bimetallics of the present invention is a heterogeneous catalyst, and the separation efficiency and catalytic activity are significantly improved.

[0012] The present invention also protects a method for preparing the above-mentioned multi-level porous MOFs material containing CuRu bimetallic, which is characterized by comprising the following steps:

[0013] S1. dissolving a copper salt and a ruthenium salt in a solvent to obtain a mixed solution A; dissolving an organic ligand in a solvent to obtain a mixed solution B;

[0014] S2. After the mixed solution A and the mixed solution B are mixed evenly, the mixture is reacted at 50 to 80° C. for 10 to 20 hours, and the multi-level porous MOFs material containing CuRu bimetallic is obtained by separation and washing;

[0015] The molar ratio of the copper salt and ruthenium salt raw materials is 1:(0.05-0.20).

[0016] The inventors have found that by strictly controlling the ratio of copper salt and ruthenium salt, reaction temperature and time, it is possible to use Ru 3+ Cu at metal nodes 2+ The unsaturated sites are replaced to form a MOFs material containing a CuRu bimetallic containing a Cu-Cu, Cu-Ru and / or Ru-Ru structure. At the same time, the mesoporous structure is mainly controlled by XX. The MOFs material prepared by the preparation method of the present invention has a mesoporous structure and, as a gas adsorption separation agent, has excellent separation efficiency for the separation of propylene propane mixed gas.

[0017] Preferably, the organic ligand is 1,3,5-trimethylbenzenecarboxylic acid (H3BTC).

[0018] Preferably, in step S2., the reaction is carried out at 60-80° C. for 15-18 hours.

[0019] Preferably, the molar ratio of the copper salt to the ruthenium salt is 1:(0.02-0.04).

[0020] Preferably, in step S1., the solvent is a mixture of N,N-dimethylacetamide and water in a volume ratio of 1:0.1 to 0.4.

[0021] More preferably, in step S1., the solvent is a mixture of N,N-dimethylacetamide and water in a volume ratio of 1:0.2-0.3.

[0022] Optionally, the copper salt is Cu(NO3)2 and / or Cu(Ac)2.

[0023] Optionally, the ruthenium salt is one or more of Ru(NO3)3, RuCl3 or Ru(Ac)3.

[0024] Preferably, in step S2., the washing is performed using an ethanol aqueous solution.

[0025] More preferably, in step S2., the washing is firstly washing with an ethanol aqueous solution and then washing with acetone.

[0026] Unreacted starting materials can be removed by washing.

[0027] The present invention also protects the use of the multi-level porous MOFs material containing CuRu bimetal as a gas adsorption separation agent in the field of propylene propane mixed gas separation.

[0028] The present invention also protects the application of the multi-level porous MOFs material containing CuRu bimetal in the field of bioinorganic chemistry, oxidation reaction, isomerization reaction, hydrogenation reaction and reforming reaction.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention adopts Ru 3+ Introduced into the Cu-BTC framework metal node, using Ru 3+ Replace Cu at metal nodes 2+ Unsaturated sites are formed to form a MOFs material containing CuRu bimetallics and containing Cu-Cu, Cu-Ru and / or Ru-Ru structures, and the MOFs material also has mesopores, which is a multi-level porous MOFs material. The multi-level porous MOFs material containing CuRu bimetallics of the present invention is a heterogeneous catalyst, and the separation efficiency and catalytic activity are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The powder XRD diffraction patterns of compound 5 and Cu-BTC and the simulated diffraction patterns;

[0032] Figure 2 is the SEM image of compound 5;

[0033] Figure 3 N2 adsorption-desorption curve and pore size distribution curve of compound 5;

[0034] Figure 4 N2 adsorption-desorption curve and pore size distribution curve of Cu-BTC;

[0035] Figure 5 Schematic diagram of the framework structure of compound 5;

[0036] Figure 6 Schematic diagram of the dinuclear metal node structure of compound 5;

[0037] Figure 7 (a) is the SEM image of compound 5. Figure 7 (b) is the Cu metal distribution mapping diagram of compound 5. Figure 7 (c) is the Ru metal distribution mapping diagram of compound 5;

[0038] Figure 8 (a) is the room temperature propylene propane adsorption breakthrough curve of Cu-BTC. Figure 8 (b) is the room temperature propylene propane adsorption breakthrough curve of compound 5. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with specific implementation modes.

[0040] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "top", "bottom", "inside", "outside" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the drawings, they are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, the terms describing the positional relationship in the drawings are only used for illustrative purposes and cannot be understood as limitations on this patent.

[0041] In addition, if there are terms such as "first" and "second", they are only used for descriptive purposes, mainly to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components, and cannot be understood as indicating or implying relative importance.

[0042] The raw materials in the embodiments can be obtained commercially;

[0043] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the present technical field.

[0044] Example 1

[0045] The present invention provides a MOFs material, and the preparation method is as follows:

[0046] S1. The metal precursors Cu(NO3)2·3H2O, Cu(Ac)2·H2O, and Ru(Ac)3 (about 1.50 mmol in total, wherein the molar ratio of copper salt to ruthenium salt in the synthetic raw materials is 1:0.10) are placed in a polytetrafluoroethylene reactor lining, and about 10 mL of a mixed solvent of analytical grade DMA and distilled water (volume ratio 1.0:0.2) is immediately added, and then stirred for 2.0 hours to completely dissolve all the metal salts at room temperature to obtain a solution of double metal ions, namely, mixed solution A;

[0047] 1.00 mmol of organic ligand H3BTC was dissolved in 6 mL of a mixed solvent of DMA and distilled water (volume ratio 1.0:0.2), and stirred to fully dissolve to obtain a mixed solution B;

[0048] S2. Mixing the mixed solution A and the mixed solution B, stirring for about 1.5 hours, allowing them to be fully mixed at room temperature, then the mixed solution was placed in a sealed polytetrafluoroethylene reactor and heated in an oven at 75 ° C for 10 hours;

[0049] The reactor was taken out and cooled naturally to room temperature. The product was collected by centrifugation. The product was then washed 5 times with a mixture of ethanol and water (the volume ratio of ethanol to water was 1:1) to remove the unreacted precursor. The product was then washed 2 times with acetone and centrifuged to obtain a MOFs material containing a CuRu bimetallic compound named Compound 1 with a chemical formula of [Cu 2.907 Ru 0.093 (BTC)2I] n , n is an integer > 10000, I is NO3 - and / or Ac - , the yield is about 50%.

[0050] Example 2

[0051] The present invention provides a MOFs material, and the preparation method is different from that of Example 1 in that:

[0052] The heating reaction in step S2 is carried out by placing the mixture in an oven at 80° C. for 10 hours.

[0053] The MOFs material obtained in this example contains CuRu bimetallic and is named as compound 2, with the chemical formula [Cu 2.913 Ru 0.087 (BTC)2I] n , n is an integer > 10000, I is NO3 - and / or Ac - , the yield is about 53%.

[0054] Example 3

[0055] The present invention provides a MOFs material, and the preparation method is different from that of Example 1 in that:

[0056] The heating reaction in step S2 is carried out by placing the mixture in an oven at 85° C. for 15 hours.

[0057] The MOFs material obtained in this example contains CuRu bimetallic and is named as compound 3, with the chemical formula [Cu 2.904 Ru 0.096 (BTC)2I] n , n is an integer > 10000, I is NO3 - and / or Ac - , the yield is about 43%.

[0058] Example 4

[0059] The present invention provides a MOFs material, and the preparation method is different from that of Example 1 in that:

[0060] Ru(Ac)3 was replaced by RuCl3, and the volume ratio of DMA and H2O = 1.0:0.4.

[0061] The heating reaction in step S2 is carried out by placing the mixture in an oven at 80° C. for 9 hours.

[0062] The MOFs material obtained in this example contains CuRu bimetallic and is named as compound 4, with the chemical formula [Cu 2.943 Ru 0.057 (BTC)2I x ] n , n is an integer > 10000, I is Ac - 、NO3 - and / or Cl - , the yield is about 49%.

[0063] Example 5

[0064] The present invention provides a MOFs material, and the preparation method is different from that of Example 1 in that:

[0065] The metal precursors are Cu(NO3)2·3H2O, Ru(Ac)3 and RuCl3.

[0066] The heating reaction in step S2 is carried out by placing the mixture in an oven at 80° C. for 12 hours.

[0067] The MOFs material obtained in this example contains CuRu bimetallic and is named as compound 5, with the chemical formula [Cu 2.951 Ru 0.049 (BTC)2I] n , n is an integer > 10000, I is Ac -、NO3 - and / or Cl - , the yield is about 57%.

[0068] Example 6

[0069] The present invention provides a MOFs material, and the preparation method is different from that of Example 1 in that:

[0070] The metal precursors are Cu(NO3)2·3H2O, Cu(Ac)2·H2O, Ru(Ac)3, and RuCl3, and the molar ratio of Cu(NO3)2·3H2O, Cu(Ac)2·H2O, Ru(Ac)3, and RuCl3 in the synthetic raw materials is 0.70:0.20:0.03:0.07.

[0071] The heating reaction in step S2 is carried out by placing the mixture in an oven at 70° C. for 13 hours.

[0072] The MOFs material obtained in this example contains CuRu bimetallic and is named as compound 6, with the chemical formula [Cu 2.949 Ru 0.051 (BTC)2I] n , n is an integer > 10000, I is Ac - , Cl - and / or NO3 - , the yield is about 55%.

[0073] Comparative Example 1

[0074] This comparative example provides a MOFs material, and the preparation method is as follows:

[0075] S1. The metal precursor Cu(NO3)2·3H2O (about 1.50 mmol in total) was placed in a polytetrafluoroethylene-lined reactor, and about 16 mL of a mixed solvent of analytical grade DMA and distilled water (volume ratio 1.0:0.4) was immediately added, and then stirred for 2.0 hours to completely dissolve all metal salts at room temperature to obtain a solution of double metal ions, namely, mixed solution A;

[0076] 1.00 mmol of organic ligand H3BTC was dissolved in 6 mL of a mixed solvent of DMA and distilled water (volume ratio 1.0:0.2), and stirred to fully dissolve to obtain a mixed solution B;

[0077] S2. The mixed solution A and the mixed solution B were mixed and stirred for about 1.5 hours to allow them to be fully mixed at room temperature. Subsequently, the mixed solution was placed in a sealed polytetrafluoroethylene reactor and heated in an oven at 80 ° C for 20 hours;

[0078] The reactor was taken out, cooled naturally to room temperature, and the product was collected by centrifugation; then washed 5 times with a mixture of ethanol and aqueous solution (the volume ratio of ethanol and water was 1:1) to remove unreacted precursors, and then washed twice with acetone, and MOFs material was obtained by centrifugation. The MOFs material contained Cu single metal and was named Cu-BTC, with a yield of about 70%.

[0079] Performance Testing

[0080] XRD characterization was performed on compound 5 obtained in Example 5 and Cu-BTC obtained in Comparative Example 1. The XRD instrument was from Rigaku Corporation of Japan, model Ultima IV, Cu target, and the powder sample was tested after grinding. The 2θ scanning angle range was 5-60 degrees, the voltage was 40 kV, the current was 40 mA, and the scanning speed was 10 degrees per minute.

[0081] like Figure 1 As shown, it can be seen that the spectrum of compound 5 is basically consistent with the spectrum of Cu-BTC and the simulated spectrum, and no extra diffraction peaks are formed, indicating that no extra phases are generated.

[0082] The compound 5 obtained in Example 5 was characterized by scanning electron microscopy (SEM). The SEM instrument was from Hitachi High-Technologies Corporation, Japan, model number was Regulus 8220. The powder sample was treated with gold spraying. The test voltage was 10.0 kV and the scale was 3.00 μm. The results are shown in FIG. Figure 2 As shown, it can be seen that the particle size distribution of compound 5 is in the range of 1 to 3 μm.

[0083] The N2 adsorption-desorption curve and pore size distribution of compound 5 are shown in Figure 3 As shown in Figure 2, the specific surface area of ​​compound 5 is calculated to be 1189 m 2 ·g -1 The pore size distribution is that micropores and mesopores coexist. That is, the MOFs material prepared in the embodiment of the present application has a multi-level pore structure. The N2 adsorption-desorption curve and pore size distribution of Cu-BTC in comparative example 1 are as follows Figure 4 As shown. According to calculation, the specific surface area of ​​Cu-BTC is 1780m 2 ·g -1 , but there are only micropores in the pore size distribution, and no mesopores are generated.

[0084] The schematic diagram of the framework structure of the multi-level porous MOFs material containing CuRu bimetallic prepared by the present invention is as follows Figure 5 As shown, the schematic diagram of the two-core metal node structure is as follows Figure 6 As shown, it can be seen that it contains three metal node structures of Cu-Cu, Cu-Ru and / or Ru-Ru.

[0085] according to Figure 7 From the SEM image and the metal distribution mapping diagram, it can be seen that the Ru doped and introduced by the preparation method of the present invention is highly dispersed at the atomic or nanometer level.

[0086] The activated compound 5 was used in the separation experiment of propylene and propane mixed gas (volume ratio 50:50). At room temperature 20°C and mixed gas flow rate of 4 mL / min, propane gas flowed out first at about 2750 seconds, and then propylene gas flowed out at about 4000 seconds. The separation purity was always above 99.8% ( Figure 8 b). When Cu-BTC is used as the catalyst, propane gas flows out first at about 2230 seconds, followed by propylene gas at about 3130 seconds. The separation purity reaches more than 92.0% ( Figure 8 a). The MOFs material of Example 5 of the present application is used to separate propylene and propane, and the separation efficiency is improved by more than 1.35 times compared with the Cu-BTC of Comparative Example 1. This indicates that the introduction of Ru heterometallic doping into the metal nodes of the parent Cu-BTC framework and the formation of multi-level pores have a significant effect on improving the propylene and propane separation performance of the material.

[0087] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. Application of multi-level porous MOFs material containing CuRu bimetallic as gas adsorption separation agent in the field of propylene propane mixed gas separation, characterized in that: The hierarchical porous MOFs material has the chemical formula [Cu 3-x Ru x (BTC)2I x n , where 0.03 < x < 0.15, n is an integer greater than 10000, and I is Cl - , NO3 - , Ac - and at least two of them;​ The preparation method of the multi-level porous MOFs material comprises the following steps: S1. dissolving a copper salt and a ruthenium salt in a solvent to obtain a mixed solution A; dissolving an organic ligand in a solvent to obtain a mixed solution B; S2. After the mixed solution A and the mixed solution B are evenly mixed, the mixture is reacted at 50-80° C. for 10-20 hours, and the multi-level porous MOFs material containing CuRu bimetallic is obtained after separation and washing; The molar ratio of the copper salt and ruthenium salt raw materials is 1:(0.05-0.20).

2. The application according to claim 1, characterized in that: The organic ligand is H3BTC.

3. The application according to claim 1, characterized in that: In step S2., the reaction is carried out at 60-80° C. for 15-18 hours.

4. The use according to claim 1, characterized in that: The molar ratio of the copper salt to the ruthenium salt is 1:0.

05.

5. The use according to claim 1, characterized in that: In step S1., the solvent is a mixture of N,N-dimethylacetamide and water in a volume ratio of 1:0.1-0.

4.

6. The use according to claim 1, characterized in that: The copper salt is Cu(NO3)2 and / or Cu(Ac)2.

7. The use according to claim 1, characterized in that: The ruthenium salt is one or more of Ru(NO3)3, RuCl3 or Ru(Ac)3.

8. The use according to claim 1, characterized in that: The washing is performed using an ethanol aqueous solution.